1992
DOI: 10.1098/rsta.1992.0001
|View full text |Cite
|
Sign up to set email alerts
|

On the amplitude dynamics and crisis in resonant motion of stretched strings

Abstract: An N -mode truncation of the equations governing the resonantly forced nonlinear motions of a stretched string is studied. The external forcing is restricted to a plane, and is harmonic with the frequency near a linear natural frequency of the string. The method of averaging is used to investigate the weakly nonlinear dynamics. By using the amplitude equations, which are a function of the damping and the frequency of excitation, it is shown that to O(e) , only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…They found the associated stable periodic dynamics and mention that no recurrent response is expected past the simple case of the Shilnikov bifurcation. Moreover, these authors observed the merging of two reflectionally symmetric orbits into a single symmetric orbit [Bajaj & Johnson, 1992;Johnson & Bajaj, 1989]. Our results (a) are very similar, but they are for an inclined cable, which differs from a horizontal string by the presence of a plane of inclination and the associated specific difference between in-plane and out-of-plane motion -not to mention the differences in parameter values between a string and a bridge cable.…”
Section: Influence Of ω/ω 2 and Shilnikov Homoclinic Bifurcationsupporting
confidence: 76%
See 4 more Smart Citations
“…They found the associated stable periodic dynamics and mention that no recurrent response is expected past the simple case of the Shilnikov bifurcation. Moreover, these authors observed the merging of two reflectionally symmetric orbits into a single symmetric orbit [Bajaj & Johnson, 1992;Johnson & Bajaj, 1989]. Our results (a) are very similar, but they are for an inclined cable, which differs from a horizontal string by the presence of a plane of inclination and the associated specific difference between in-plane and out-of-plane motion -not to mention the differences in parameter values between a string and a bridge cable.…”
Section: Influence Of ω/ω 2 and Shilnikov Homoclinic Bifurcationsupporting
confidence: 76%
“…It is not shown here, but we remark that such an isolated branch was also found for a vibrating horizontal string in [Bajaj & Johnson, 1992;Johnson & Bajaj, 1989]. The bifurcating periodic solutions undergo period-doubling at the curves P D 11 and P D 21 shown in Fig.…”
Section: Bifurcation Diagram Of Periodic Solutions In the (ω/ω 2 ∆/mentioning
confidence: 86%
See 3 more Smart Citations